آليات تشجيع الاستثمار الأجنبي في القانون الجزائري - جداينى، زكية (جامعة الجزائر1 بن يوسف بن خدة, 2019)
Since the second half of the twentieth century, countries have tended to adopt investment as a strategic option to drive growth and development as well as stimulate economic movement, especially with regard to foreign investment. Algeria has tried to create an appropriate environment through the establishment of an institutional framework dedicated to the legislator's desire to provide facilities to investors, especially foreigners, to invest in all fields, to support and follow up these investments, and to develop several mechanisms to encourage them through the embodiment of legal protection on their investment project, as well as creating an appropriate investment environment that will be able to face all kinds of risks that may affect the investment project, whether commercial or political, while seeking to support investment with fiscal and customs incentives, as well as the allocation of industrial estates and infrastructure to receive The foreigner will produce and bring in more investments for growth in the national economy.
اتجهت الدول منذ النصف الثاني من القرن العشرين إلى تبني الاستثمار كخيار استراتيجي لدفع عجلة النمو ومسيرة التنمية وكذا تنشيط الحركة الاقتصادية، لاسيما فيما يخص الاستثمار الأجنبي. وقد حاولت الجزائر خلق مناخ ملائم من خلال إنشاء إطار مؤسساتي يكرس إرادة المشرع في منح تسهيلات للمستثمرين لاسيما الأجانب للاستثمار في كل المجالات، والقيام على دعم ومتابعة تلك الاستثمارات، ووضع آليات عديدة لتشجيعها من خلال تجسيد حماية قانونية تتمثل في ترسانة من النصوص تحقق للمستثمر الأجنبي الاطمئنان على مشروعه الاستثماري، وكذا خلق بيئة استثمارية ملائمة تمكن من مواجهة كل أنواع المخاطر التي قد تصيب المشروع الاستثماري سواء كانت تجارية أو سياسية مع السعي إلى دعم الاستثمار بتحفيزات جبائية وجمركية وكذا تخصيص عقارات صناعية وبنى تحتية لاستقبال المستثمر الأجنبي، وجلب عدد أكبر من الاستثمارات من أجل النمو بالاقتصاد الوطني.
الجزء الأول: مارس 2019
Keywords: قوانين الاستثمار -- الاستثمارات الأجنبية -- القوانين والتشريعات -- الجزائر